Структура электронного учебника «Диагностика и моделирование» - Шкиль, A. C.; Севастьянов, А. Б.; Мазур, М. С. (УАДО, 2002)
In the given work the problem of file and navigation structure of interactive tutorials is considered As an example of interactive lutorial the “Diagnostics and simulation” has been represented. Three level thematical structurization is applied. Completing of information and navigation for sites is considered.
Keywords: структура электронного учебника; образование